Rede de transgênicos e combate à fome no Brasil : um estudo de caso sobre a rede RENORBIO - Sobral, Vivianne Caroline Santos (2015)
Assuming that the use of (GMOs) in agriculture is controversial, this paper discusses one of the strongest reasons in favor of such technology: as a mean to combat hunger. To assess this joint between transgenesis and combat hunger, the RENORBIO’s researchers network (“Rede de Biotecnologia do Nordeste” - Biotechnology Network in the Northeast) has been selected to this study for stating “the use of bioscience advances to reduce hunger "as one of its interests. The present work presents a sociological point of view on the advancement of technology in agriculture, seeking to understand the progression of GM farming in crops from some reading about modern techniques. Then the question of risk and how it is produced nowadays is discussed, and, after that, the Agroecology is presented as an alternative to transgenic agricultural management. Only then, the fight against hunger is questioned, as something controversial, whose solution options depend on different worldviews. Finally, are presented some major explanations of RENORBIO, its allies, its articulations and their researches on transgenesis.